Parasitismo en huevos de araña Achaearanea tepidariorum (Koch) (Aranea: Theridiidae) en Costa Rica - Valerio, Carlos E. (1970)
Two new records of parasites of the eggs of the spider Achaearanea tepidariorum are reported: an undescribed species of a microhymenopteran, Baeus sp. (Scelionidae) and a neuropteran, Mantispa viridis (Mantispidae). Three populations of the spider were studied, of which the one on the campus of Universidad de Costa Rica was highly infested: 63.85 per cent of the to tal egg sacs collected were parasitized, about 48 per cent by Baeus sp. and about 15 per cent by the mantispid.In M. viridis one larva develops in every egg sac, utilizing nearly all the eggs present. On the other hand, Baeus sp. has one larva developing per egg, parasitizing almost 80 per cent of the eggs present in each saco This means that of all the eggs produced by A. tepidariorum, less than 50 per cent complete their normal development.Two egg sacs were found evidently parasitized by both species, which means that some of the eggs eaten by the mantispid larva had already been parasitized by the wasp. Apparently M. viridis has a definite advantage in this competitive relationship for an identical source of food, but as shown here this is not the case in nature, due probably to the relatively large size of the neu ropteran. In many cases the mantispid is probably detected and captured by the female spider while approaching or leaving the egg sac, a problem not faced by the minute wasps.The adults of M. viridis feed actively on small insects... and live ap proximately five days under laboratory conditions. Those of Baeus sp. apparently do not feed (on sugar solutions). The males live one or two days, the females between five and seven days (one female lived 14 days in the laboratory).